Construction of a Lactate-Related Prognostic Signature for Predicting Prognosis, Tumor Microenvironment, and Immune Response in Kidney Renal Clear Cell Carcinoma - Sun, Zhuolun; Tao, Wen; Guo, Xudong; Jing, Changying; Zhang, Mingxiao; Wang, Zhenqing; Kong, Feng; Suo, Ning; Jiang, Shaobo; Wang, Hanbo (Frontiers in Immunology, 2022)
Kidney renal clear cell carcinoma (KIRC) presents one of the most prevalent primary malignancy with the highly heterogeneousness in urological system. Growing evidence implies that lactate is a significant carbon source for cell metabolism and plays a vital role in tumor development, maintenance, and therapeutic response. However, the global influence of lactate-related genes (LRGs) on prognostic significance, tumor microenvironment characteristics and therapeutic response on has not been comprehensively elucidated in KIRC patients. In the present study, we collected the RNA sequencing and clinical data of KIRC from The Cancer Genome Atlas (TCGA), the E-MTAB-1980, and the GSE22541 cohorts. Unsupervised clustering of 17 differentially expressed LRGs profiles divided the samples into three clusters with distinct immune characteristics. Three genes (FBP1, HADH, and TYMP) were then identified to construct a lactate-related prognostic signature (LRPS) using the least absolute shrinkage and selection operator (LASSO) and Cox regression analyses. The novel signature exhibited excellent robustness and predictive ability of patient’s overall survival. Additionally, the constructed nomogram based on LRPS-based risk score and clinical factors (age, grade, stage and gender) had robust predictive performance. Furthermore, patients divided by risk score had distinguishable immune status, tumor mutation burden, response to immunotherapy, and sensitiveness to drugs. In conclusion, we developed a LRPS in KIRC that was closely related to the immune landscape and therapeutic response. The LRPS may guide clinicians to make more precise and personalized treatment decisions for KIRC patients.